1998
DOI: 10.1128/aem.64.9.3320-3326.1998
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Methionine to Thiols by Lactococci, Lactobacilli, and Brevibacteria

Abstract: Methanethiol has been strongly associated with desirable Cheddar cheese flavor and can be formed from the degradation of methionine (Met) via a number of microbial enzymes. Methionine γ-lyase is thought to play a major role in the catabolism of Met and generation of methanethiol in several species of bacteria. Other enzymes that have been reported to be capable of producing methanethiol from Met in lactic acid bacteria include cystathionine β-lyase and cystathionine γ-lyase. The objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(69 citation statements)
references
References 28 publications
0
68
1
Order By: Relevance
“…This activity is also strongly correlated with methanethiol and its direct oxidation products. L-Methionine aminotransferase activity, although reported in several cheese-ripening microorganisms, is not ubiquitous [5], compared to the versatile enzyme L-methionine demethiolase [5,12,24]. For instance, L-methionine aminotransferase activity was reported in cellular extracts of the bacteria B. linens, M. luteus, C. glutamicum, but was not detected in Arthrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…This activity is also strongly correlated with methanethiol and its direct oxidation products. L-Methionine aminotransferase activity, although reported in several cheese-ripening microorganisms, is not ubiquitous [5], compared to the versatile enzyme L-methionine demethiolase [5,12,24]. For instance, L-methionine aminotransferase activity was reported in cellular extracts of the bacteria B. linens, M. luteus, C. glutamicum, but was not detected in Arthrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Another important conversion route of amino acids is initiated by lyases ( Fig. 1(10)), like cystathionine b-lyase (EC 4.4.1.8), which is able to convert methionine to methanethiol [41][42][43]. Threonine aldolase (EC 4.1.2.5) ( Fig.…”
Section: (Bio-)chemical Routes Leading From Proteins To Flavourmentioning
confidence: 99%
“…The homotetrameric enzyme with a M w of 170 kDa is PLP dependent and has a pH optimum of 7.5 [126]. The enzyme is also slightly active under cheese ripening conditions, but is also susceptible for proteolysis [41,126]. Amarita et al [133][134][135] studied the role of this lyase and found that disruption of the gene coding for this enzyme resulted in an almost complete abolishment of the production of volatile sulphur compounds in this strain, indicating the importance of this enzyme in the formation of sulphur compounds in B. linens.…”
Section: Lyase Pathwaymentioning
confidence: 99%
“…Sulfur compounds (particularly methanethiol and hydrogen sul¢de) are components of cheddar cheese £avor [6,8,9], and enzymes involved in the metabolism of sulfur containing amino acids may therefore have a major role in the formation of £avor compounds during cheese ripening [10,11]. Cystathionine lyase, which is involved in methionine biosynthesis [12], has been puri¢ed from a number of organisms, including Lactococcus lactis ssp.…”
Section: Introductionmentioning
confidence: 99%